2011
DOI: 10.1063/1.3577577
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of electric fields and plasma barodiffusion on the inertial confinement fusion database

Abstract: The generation of strong, self-generated electric fields (GV/m) in direct-drive, inertial-confinement-fusion (ICF) capsules has been reported [Rygg et al., Science 319, 1223 (2008); Li et al., Phys. Rev. Lett. 100, 225001 (2008)]. A candidate explanation for the origin of these fields based on charge separation across a plasma shock front was recently proposed [Amendt et al., Plasma Phys. Controlled Fusion 51 124048 (2009)]. The question arises whether such electric fields in imploding capsules can have observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 14 publications
(40 reference statements)
1
48
0
Order By: Relevance
“…Further investigations found that non-maxwellian ion distributions resulting from shock front kinetic effects that deplete the ion distribution of fast particles [10][11][12][15][16][17][18] may alter the hydrodynamics and thermonuclear yield of ICF capsules. Other studies suggest that capsule yield can be diminished by kinetic effects associated with strong self-generated electric fields which can broaden the shock fronts [19,20]. With that, the physics of ICF capsules being possibly subject to strong non-equilibrium effects provides a strong motivation to develop a kinetic simulation code that is capable to fully resolve shock fronts in all regions of the capsules.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations found that non-maxwellian ion distributions resulting from shock front kinetic effects that deplete the ion distribution of fast particles [10][11][12][15][16][17][18] may alter the hydrodynamics and thermonuclear yield of ICF capsules. Other studies suggest that capsule yield can be diminished by kinetic effects associated with strong self-generated electric fields which can broaden the shock fronts [19,20]. With that, the physics of ICF capsules being possibly subject to strong non-equilibrium effects provides a strong motivation to develop a kinetic simulation code that is capable to fully resolve shock fronts in all regions of the capsules.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple ion species are not treated separately: the ion mass and charge are set as a weighted average of the individual species. Recent experimental and theoretical work has questioned the validity of the average-ion assumption [5][6][7][8][9][10][11][12][13][14][15]. Anomalous reduction of the compression-phase nuclear yield has been observed in implosions filled with multiple fuel species, such as deuteriumhelium-3 (D 3 He) [5], DT [6], and other combinations [7,8].…”
mentioning
confidence: 99%
“…[30]. Equation (2) reduces to the familiar expression in the weakly coupled limit, in which Ξ αβ becomes the conventional Coulomb logarithm ln Λ [38].…”
Section: Evaluation Of the Transport Coefficientsmentioning
confidence: 99%
“…In particular, it has been suggested that strong background gradients introduced during the implosion can separate fusion fuel constituents, resulting in yield degradation [1][2][3][4][5][6][7][8][9][10][11][12][13]. The same ion diffusion mechanisms that govern species separation in the fuel underlie mixing at the shell/fuel interface [14][15][16][17][18][19][20], as well as at the inner boundary of the hohlraum [21].…”
Section: Introductionmentioning
confidence: 99%